STUDY OF QUIESCENT GALAXIES ACROSS REDSHIFT RANGE OF 2 < Z < 7 USING JWST AND HST DATA - Saputra Haryana, Novan
Galaxies formed approximately 300 million years after the Big Bang (cosmic dawn epoch). After formation, galaxies underwent evolution parallel to the evolution of the universe. The evolution of galaxies encompasses various aspects, including the star formation rate (SFR) within them. In their early stages, galaxies formed stars at a much higher rate than present, reaching a peak before declining over time. The processes and mechanisms causing this slowdown in star formation rate remain a prominent topic of study in astrophysics. In this research, imaging and photometric data from the James Webb Space Telescope (JWST) and the Hubble Space Telescope (HST) spanning the redshift range 2 < z < 7 were used to obtain the distribution of quiescent galaxies against redshift and mass, and the star formation history (SFH) in these quiescent galaxies. Quiescent galaxies were selected using UVJ and SFR-mass diagrams. The analysis process involve mass and SFR obtained from spectral energy distribution (SED) fitting using piXedfit. SFHs are derived from SED fitting using dense basis. It was found that the number density of passive galaxies increases with decreasing redshift, tending to peak at log(M/M?) ? 10.5. Additionally, for the range 2.0 < z < 2.5, a second peak in the density distribution was observed at log(M/M?) ? 8.9. Regarding SFH, an analysis of the median SFH values across all redshift and mass ranges was conducted, revealing an initial rise, reaching a peak, and then declining. It was found that the rising phase in low-mass galaxies is shorter, while the decline phase is longer. Conversely, high-mass galaxies experience a rapid rise phase followed by a longer decline compared to low-mass galaxies. However, it was observed that the rate of increase in SFR towards the peak, and the rate of decline thereafter, is always higher in high-mass galaxies. The obtained results support the downsizing scenario, which states that large-mass galaxies will evolve faster than smallmass galaxies.